Adsorption-based approach to determine the size and mass of humic acids molecules - Yuri I Tarasevich; Maryna Yu Tryfonova; Svitlana A Dolenko; Eugene V Aksenenko (Adsorption Science & Technology)
The state of sodium humate in aqueous solution and on a solid surface is studied using various methods. It is shown that in aqueous solution at neutral pH and low ionic strength this substance exists in an associated state. The values of molecular mass of the molecules in the preparation studied (Aldrich) are determined to be 1, 3–6 and 15 kDa. A new adsorption-based approach for initial estimation of the molecular mass and size of humic acid molecules is proposed, which can be used instead of any specific sophisticated equipment. The size of the molecules of the studied preparation estimated in this way (in the range of 2.3 to 9.0 nm), agree well with data obtained by chromatographic and electron microscopic measurements, which confirm the reliability of the proposed method.